Bluetooth Based Home Control and Real-Time Energy Consumption Monitoring System through Smartphone - Rahayu, Yusnita; Hidayat, Muhammad Ibnu (International Journal of Electrical, Energy and Power System Engineering, 2019)
Energy consumption is one of the most important, for it is necessary to control the use of home lighting as needed. Monitoring is important, in order to know the quality of electricity supply in the system, identifying disruption events, and to calculate the amount of electrical energy consumption periodically. To achieve the objectives mentioned above, two schemes for home control and monitoring the electrical quantities in real-time have been developed. The first scheme presents Bluetooth based home control. It uses an HC-05 Bluetooth module and Bluetooth Controller mobile application for switching on / off the appliances. Relay and LEDs are used as loads to demonstrate the working of the system. This system is based on Arduino Uno microcontroller board. Arduino Integrated Development Environment (IDE) is used for developing the necessary software. The second scheme uses the current sensor ACS712-20A for monitoring of voltage, current, and energy consumption. The measurement results include voltage, current, power, and the amount of energy consumption that is displayed by LCD 16*2.